Cost-effectiveness of adding measurement of Chlamydia trachomatis infection and serology to trachoma prevalence surveys in Tanzania and Mozambique. - Emily C Decker; Molly W Adams; William E Oswald; Rebecca M Flueckiger; Jeremiah M Ngondi; Mawo Fall; Ezgi E Yilmaz; Lisa C Brooks; George Kabona; Henis Mior Sitoe; Mabula Kasubi; Tamimo Momade; et al. (PLoS Neglected Tropical Diseases, 2025)
Background Accurate methods to measure trachoma prevalence are critical to monitor progress and guide mass drug administration as countries near elimination. Currently, countries conduct trachoma prevalence surveys via clinical examination using the simplified trachoma grading system. Grading can have reduced accuracy in low prevalence settings, potentially resulting in errors. Adding ocular swabbing and Chlamydia trachomatis (Ct) infection testing and dried blood spot (DBS) collection and testing can be more sensitive and specific methods for trachoma identification, with potential cost-saving and information benefits. While previous studies have examined the costs of trachoma prevalence surveys, we present the first costing and cost-effectiveness analysis of enhanced trachoma prevalence surveys with ocular swabs and DBS in addition to grading. Methodology/principal findings We calculated the incremental financial cost of enhanced trachoma prevalence surveys with swabs, DBS, and grading using expenditure records from four districts in Tanzania and four districts in Mozambique in 2022. In Tanzania, the cost per cluster of an enhanced survey was $2,337.39 compared to $459.75 for a standard survey. In Mozambique, the cost per cluster of an enhanced survey was $2,147.12, compared to $1,381.46 for a standard survey. We calculated the incremental cost-effectiveness ratio for each method, defined as the ratio of incremental cost to additional instances of trachoma indicators identified, and explored variation in cost-effectiveness via sensitivity analyses. Adding swabs, DBS, or both was cost-increasing and more effective at identification of trachoma indicators than grading alone. In Tanzania, swabs were the most cost-effective method, while DBS was more cost-effective in Mozambique. Swabs and DBS were less cost-effective when combined than individually. The main factor determining cost-effectiveness was sensitivity. Conclusions/significance Adding swabs or DBS to trachoma prevalence surveys can be viable, cost-effective methods for identifying trachoma indicators. The additional costs are commensurate with additional information that would support elimination efforts.